Investigating the drivers of consumer acceptance and response of SMS advertising - Dix, Steve; Phau, Ian; Jamieson, Kyle; Shimul, Anwar Sadat (2015)
This study tests five potential drivers underlying the acceptance of SMS advertising. After developing a scale to measure behavioral responses to SMS advertising, the relationships between the acceptance of SMS advertising, intention to receive SMS advertising and behavioral responses to SMS advertising are tested. A convenience sampling method was employed. Survey questionnaires were distributed across Western Australia. The return yielded 203 usable questionnaires from the respondents. Several factors emerge as significant drivers of acceptance of SMS advertising including utility of SMS advertisements, context of SMS advertisements and attitudes to advertising in general. Contrary to expectation, control over SMS advertisements did not emerge as a significant driver for acceptance of SMS advertising. Trust in advertisers and laws did not emerge as a significant driver of the acceptance of SMS advertising among Australian respondents. Advertisers who pursue consumer acceptance should strive to build utility and context considerations into their SMS campaigns. Future research opportunities include testing the drivers of SMS advertising to further investigate the impact of control and trust on acceptance of SMS advertising in other countries where the SMS advertising has not been explored yet.